Dominican Chant and Dominican Identity - Smith, Innocent (Religions, 2014)
The Order of Preachers possesses a venerable chant tradition that dates back to the thirteenth century. This essay describes Dominican chant, showing how it developed as a consequence of the attitudes to the liturgy expressed in the Ancient Constitutions of the Order of Preachers. These constitutions stressed that the liturgy was to be performed with careful attention to bodily posture, with a succinctness and brevity that would allow time for study and preaching, and with gradations of solemnity that would express the inner hierarchy of parts of the liturgy and of the liturgical year. After the initial development of the repertoire, Dominican chant has gone through periods of decline and revival, which are briefly traced in this article together with a consideration of the place of the chant in the contemporary practice of the Order. Throughout the last eight centuries, the chant of the Order of Preachers has played an important role in the inculcation and preservation of Dominican identity within the Order and in the lives of individual friars and sisters.